Comparative efficacy and safety of ticagrelor vs. prasugrel in patients undergoing PCI for NSTE-ACS. Results of the prospective ALKK-Registry. (3rd October 2022) - Zeymer, U; Hochadel, M; Schaechinger, V; Zahn, R
Abstract: Background: Dual antiplatelet therapy with aspirin and a P2Y12 inhibitor has become standard of care for patients with NSTE-ACS. Guidelines recommend prasugrel and ticagrelor over clopidogrel. In the ISAR-5 trial prasugrel was superior to ticagrelor in NSTE-ACS patients. We evaluated the outcome of patients undergoing PCI for NSTE-ACS in a large number of patients in real life and compared patients treated with prasugrel and ticagrelor. Methods: We used the data of the prospective German ALKK-PCI registry and included patients treated with prasugrel or ticagrelor and undergoing PCI for NSTE-ACS treated in 42 centers. Baseline variables, procedural features, antithrombotic therapies and in-hospital outcomes were centrally collected and analysed. Patients with cardiogenic shock were excluded. Results: Between 2011 and 2020 a total of 7888 patients <75 years without prior stroke undergoing PCI for NSTE-ACS were included. Of these 4905 (62.2%) patients were treated with ticagrelor and 2983 (37.8%) were treated with prasugrel. Baseline characteristics, procedural features and in-hospital outcomes are given in the table. Conclusion: In clinical practice in patients with NSTE-ACS undergoing PCI ticagrelor was used more often than prasugrel. Ticagrelor treated patients were older and had more comorbidities. Despite this higher risk profile in ticagrelor patients the in-hospital mortality and the short-term safety profile were comparable in both groups. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Institut für Herzinfarktforschung Ludwigshafen